Bleak House - Dickens, Charles. 1812-1870 (Vintage Books, 2012)
"In Bleak House, competing claims of love and inheritance--complicated by murder--have given rise to a costly and decades-long legal battle that one litigant refers to as 'the family curse.' The insidious London fog that rises from the river Thames and seeps into the very bones of the characters symbolizes the pervasive corruption of the legal system and the society that supports it, targets of Dickens's satirical wrath."--P. [2] of cover.